Conservation of a clay fragments with the Strappo technique in the Choquequirao Archaeological Site - Pinchaunuyoc Sector, Cusco – Peru - Yepez Peña, Miguel Angel (2020)
The coatings of clay in the precincts of pre-hispanic built with elements of stone, are atypical, and by their various characteristics present a problem in their conservation and intervention, from the procedure to run as the choice of the appropriate technique to perform the same. The execution of the work of Restoration and Conservation carried out to the fragments of clay located in the Enclosure Nº 01 of the Archaeological Set of Choquequirao – Sector Pinchaunuyoc, allows us to evaluate the techniques of Consolidation, Strappo, and Mounting made to retrieve mud plaster original, which show the constructive technique used in this enclosure of the archaeological site, and the importance of their intervention on the content of the historical and heritage value that represents. This is to establish processes for the conservation done to safeguard the cultural heritage sector Pinchaunuyoc, where we used this system of intervention that allowed the separation of three fragments of coating clay in a single piece, thereby enabling the execution of the restoration works and reconstruction of structural walls of the enclosure N° 01 to subsequently perform the work of consolidation and strappo of fragments of mud and the mount in its original location.